Pengenalan Budidaya Lebah Trigona di Desa Arga Indah Satu Kabupaten Bengkulu Tengah - Gunggung Senoaji; Nani Nuryatin; Agung Hasan Lukman; Elvi Susanti (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
Trigona bee cultivation will produce honey that is beneficial for health and can be a source of community income. This activity is very suitable to be applied in rural areas that have a green environment with various types of plants. This community service activity is intended to introduce the community in Arga Indah Satu Village to trigona bee cultivation. By introducing this trigona bee cultivation, it is hoped that it can produce pure honey and improve the quality of the environment by planting various kinds of bee food plants. In this service activity, the methods used are problem observation, preparation of tools and materials, counseling, and demonstration of bee-feeding plants. After the completion of this service, it is hoped that the community will have good knowledge about trigona bee cultivation and be able to apply their knowledge in their respective yards. The results of this community service are increasing the knowledge of the village community about trigona bee cultivation, and improving the quality of the environment through planting with various types of bee feed plants. The results of trigona bee cultivation can be a new source of income